3D meso-scale modelling of foamed concrete based on X-ray Computed Tomography. (10th November 2018) - Nguyen, Tuan; Ghazlan, Abdallah; Kashani, Alireza; Bordas, Stéphane; Ngo, Tuan
Highlights: The paper presents the in situ compression test-XCT scan of foamed concrete. The meso-scale modelling is directly reconstructed from XCT images. Failure mechanism of foamed concrete is elucidated by XCT scan and the meso-scale modelling. The meso-scale simulation shows a good agreement with the observation from XCT scan. The paper provides a comprehensive framework to understand the behaviour of foamed concrete. Abstract: Foamed concrete has been widely used in infrastructure construction and poses new challenges to design and modelling. This paper investigates the behaviour of foamed concrete with the help of X-ray Computed Tomography (XCT), which is capable of characterising the microstructure of foamed concrete. An in situ compressive test-XCT scan is carried out to observe the failure mechanism of foamed concrete by XCT when subjected to compression load. A meso-scale simulation based on XCT images is conducted to simulate the behaviour of foamed concrete. An algorithm that directly reconstructs the meso-scale model from XCT images is developed. The experimental and numerical results show that foamed concrete exhibits a significant change in mechanical behaviour; it is less brittle compared to the response of dense samples. However, the reduction in the level of brittleness is accompanied by a significant decrease in compressive strength. Failure development inside samples is successfully captured by the XCT scan and the meso-scale modelling. The topology of foamed structures, in particular the chain of interconnected pores, influences the failure mechanism of foamed concrete. The combination of XCT scan and meso-scale modelling provides a comprehensive framework to understand the mechanical behaviour of foamed concrete.